A review on the Effect of the Antibiotic Mupirocin in the Treatment of Staphylococcus aureus Infections: the Mechanism of Antimicrobial Action, Antibiotic Resistance and its Eepidemiology - A Sharifi; M Moeindoost; R Dehbanipour (Armaghane Danesh Bimonthly Journal, 2025)
Background & aim: Mupirocin (MUP) is a natural drug derived from crotonic acid that was first isolated from Pseudomonas fluorescens by Fuller et al. This antibiotic has a different chemical structure and mechanism of action and is a combination of pseudomonic acid A-D. Its mechanism of action is to inhibit protein synthesis by binding to bacterial isoleucyl tRNA synthetase. This antibiotic is often used to treat skin and soft tissue infections caused by Staphylococcus aureus isolates. Therefore, the aim of the present study was to determine and investigate the effectiveness of the antibiotic mupirocin in the treatment of Staphylococcus aureus infections: its antimicrobial mechanism of action, antibiotic resistance, and epidemiology.